Targeting Apolipoprotein E/Amyloid β Binding by Peptoid CPO_Aβ17-21 P Ameliorates Alzheimer’s Disease Related Pathology and Cognitive Decline - Shan Liu (Nature Portfolio, 2017)
Abstract Inheritance of the apolipoprotein E4 (apoE4) genotype has been identified as the major genetic risk factor for late onset Alzheimer’s disease (AD). Studies have shown that apoE, apoE4 in particular, binds to amyloid-β (Aβ) peptides at residues 12-28 of Aβ and this binding modulates Aβ accumulation and disease progression. We have previously shown in several AD transgenic mice lines that blocking the apoE/Aβ interaction with Aβ12-28 P reduced Aβ and tau-related pathology, leading to cognitive improvements in treated AD mice. Recently, we have designed a small peptoid library derived from the Aβ12-28 P sequence to screen for new apoE/Aβ binding inhibitors with higher efficacy and safety. Peptoids are better drug candidates than peptides due to their inherently more favorable pharmacokinetic properties. One of the lead peptoid compounds, CPO_Aβ17–21 P, diminished the apoE/Aβ interaction and attenuated the apoE4 pro-fibrillogenic effects on Aβ aggregation in vitro as well as apoE4 potentiation of Aβ cytotoxicity. CPO_Aβ17–21 P reduced Aβ-related pathology coupled with cognitive improvements in an AD APP/PS1 transgenic mouse model. Our study suggests the non-toxic, non-fibrillogenic peptoid CPO_Aβ17–21 P has significant promise as a new AD therapeutic agent which targets the Aβ related apoE pathway, with improved efficacy and pharmacokinetic properties.